Effect of Design Parameters on Shear Lag in Orthotropic Deck of Steel Road Bridges - Moga Cătălin; Pondichi-Alb Claudia; Suciu Mircea (Bulletin of the Polytechnic Institute of Jassy: Constructions, Architechture Section, 2021)
The phenomenon of shear lag refers to the increases of the bending stresses near the flange-to-web junctions, and the corresponding decreases in the flange stresses away from these junctions.